The prevalence of pain and analgesia use in the Australian population: Findings from the 2011 to 2012 Australian National Health Survey. Issue 11 (12th September 2017) - Miller, April; Sanderson, Kristy; Bruno, Raimondo; Breslin, Monique; Neil, Amanda L.
Abstract: Background: Opioid analgesic use and associated adverse events have increased over the last 15 years, including in Australia. Whether this is associated with increased chronic pain prevalence in the Australian population is unknown. This study aimed to estimate (1) the prevalence of chronic pain and analgesia use in the Australian population by age and sex; (2) the severity of pain in the population with chronic pain by sex; and (3) the distribution of recent pain severity in those using analgesia by age and sex. Methods: This study used cross‐sectional, nationally representative data collected by the Australian Bureau of Statistics 2011 to 2012 National Health Survey. A total of n  = 20 426 participants were included with an overall response rate of 84.8%. Weighting procedures were applied to obtain population estimates, confidence intervals, and when testing for statistical significance. Results: The prevalence of chronic and reoccurring pain (over a 6‐month period) was 15.4% (2.75 million) for Australians aged ≥15 years. Prevalence increased with age for both sexes. Significantly more females reported moderate‐to‐very severe pain overall ( P  < 0.001), and within most age groups. Recent use of opioid analgesia was reported by 12.0% of males and 13.4% of females with chronic pain. Conclusion: Chronic pain and opioid analgesic use are important public health issues in Australia. Study estimates of chronic pain and recent pain were no greater than earlier estimates. The acknowledged increase of opioid use in the literature thus appears consistent with changing treatment and/or prescribing patterns over time. Sex differences regarding pain prevalence, severity, and opioid use were apparent.